The Mediating Role of Innovation and Artificial Intelligence on SMEs Performance - Yonas Ferdinand Riwu; Klaasvakumok Jehezkielomi Kamuri; Sonia Virgarini Nawi (CV. Vocezmi Learnov, 2026)
This study aims to examine the influence of knowledge management, Artificial Intelligence (AI), and innovation on the performance of Small and Medium Enterprises (SMEs) in Indonesia, as well as to analyze the mediating roles of innovation and AI in strengthening SME performance. The study employed a quantitative approach using survey data collected from 200 SMEs across various industrial sectors in Indonesia. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the validity of the measurement model and examine the hypothesized relationships among variables. This study contributes to the literature by integrating knowledge management, AI adoption, and innovation within a unified framework to explain SME performance. It provides empirical evidence on the mediating roles of innovation and AI, highlighting their strategic importance in translating knowledge resources into superior organizational performance. The findings suggest that SME owners and managers should invest in structured knowledge management systems and AI-supported technologies to enhance decision-making, collaboration, and innovation capabilities. Policymakers are encouraged to support SMEs through training programs and technological infrastructure development to foster sustainable SME growth. This study is limited by its cross-sectional design and reliance on self-reported survey data, which may restrict causal interpretation. Future research is recommended to employ longitudinal designs, expand sample coverage, and incorporate additional contextual variables to deepen understanding of digital transformation and performance dynamics in SMEs.